1986
DOI: 10.1016/s0010-9452(86)80004-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Specialized Cognitive Function Following Changes in Hormone Levels

Abstract: Increase of follicle stimulating hormone (FSH) and luteinizing hormone (LH) in men by injection of luteinizing hormone releasing hormone (LHRH) prevented improvement in a spatial orientation test relative to a placebo condition. By contrast, performance on a fluency task was significantly increased after LHRH injection relative to the placebo condition. These data support between-subject results where FSH was negatively correlated with visuospatial skills and positively correlated with fluency. There was no ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(36 citation statements)
references
References 21 publications
4
29
1
2
Order By: Relevance
“…The importance of controlling time effects is evident in some repeated measures design studies, which analyze cognitive performance and cerebral asymmetries during the menstrual cycle (McKeever, 1995). Gordon, Corbin, and Lee (1986) demonstrated that women who started three testings of verbal and spatial tasks at their follicular phase outperformed women who started during menses. Mead and Hampson (1996) observed a pronounced left visual half field increase in accuracy and speed from the first to the second session, when subjects started in the midluteal phase.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of controlling time effects is evident in some repeated measures design studies, which analyze cognitive performance and cerebral asymmetries during the menstrual cycle (McKeever, 1995). Gordon, Corbin, and Lee (1986) demonstrated that women who started three testings of verbal and spatial tasks at their follicular phase outperformed women who started during menses. Mead and Hampson (1996) observed a pronounced left visual half field increase in accuracy and speed from the first to the second session, when subjects started in the midluteal phase.…”
Section: Discussionmentioning
confidence: 99%
“…Direct hormone measurements are a prerequisite for menstrual cycle research, as previous studies had to exclude large numbers of participants (up to 46%, Gordon et al, 1986) because hormone assays revealed that participants were not in the expected cycle phase. As a result, if some participants were tested just before or after the expected peak in estradiol and/or progesterone levels, the variability in the degree of lateralisation would be greater across participants.…”
Section: Introductionmentioning
confidence: 99%
“…Cycle phase can be estimated by counting backward to the first day of menstruation. Although this counting method has been used legitimately in some previous research, the approach has been associated with an error rate of 15 [34] to 50% [13]. Confirmation of expected hormone concentrations by radioimmunoassay (RIA) is critical for validating menstrual phase, because accuracy in determining menstrual phase is likely a major factor contributing to incongruent results across previous studies.…”
Section: Introductionmentioning
confidence: 99%